AZERBAIJAN AND GEORGIA: ASYMMETRICAL RELATIONS - MINASIAN, Sergey (CENTRAL ASIA AND THE CAUCASUS, 2014)
The relations between Georgia and Azerbaijan are a key factor in regional politics and security in the Southern Caucasus. They strongly affect economic contacts and trade, as well as the implementation of all sorts of communication and energy projects. The two countries agree on many issues of regional policy, the way ethnopolitical conflicts should be settled, and the degree to which external actors could or should be involved. Turkey’s presence in bilateral Georgian-Azeri relations is another important factor that may end in a geopolitical triangle of sorts in the Southern Caucasus. On the other hand, these relations cannot and should not be described as a formalized full-scale political, let alone, military-political alliance with corresponding mutual obligations. The author discusses these and other aspects of bilateral relations, assesses the prospects for further cooperation, and points to the possible challenges and problems that might crop up later.